The production of chicha de año, as a developmental resource at Magdalena de Cao district - Pacheco Neyra, Gianella Gabriella (2017)
This paper presents the results of an ethnographic research carried out in the district of Magdalena de Cao, located in the department of La Libertad. This work aims to contribute to the understanding of the changes generated in the production, tradition, and identity of the chicha de año makers. Chicha de año is a traditional alcoholic beverage that, along with the Lady of Cao, is one of the most emblematic elements of Magdalena de Cao. Since the arrival of institutions linked to development and enhancement projects, changes in the traditional production of Chicha de año have become more dynamic. In this process, two groups of chichi makers have been identified, the first one more open to changes in the discourse and production techniques and the second one more reluctant to them. The social an economic factors that influencing this process is analyzed.